2022
DOI: 10.1055/s-0041-1742098
|View full text |Cite
|
Sign up to set email alerts
|

Bone Remodeling after Ulna Head Replacement in Distal Radioulnar Joint Arthroplasty: A Radiographic Comparison between a Partial and a Total Ulna Head Concept

Abstract: Background Ulna head arthroplasty has become an eligible solution for injury or disease in the distal radioulnar joint. Bone resorption beneath the prosthetic head is often reported, but mechanism poorly understood. Purpose The aims were to evaluate bone remodeling and radiological instability in two conceptually different distal radioulnar joint arthroplasties: the total and the partial ulna head replacement. Patients and Methods We conducted a retrospective radiographic assessment of 51 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A newest study revealed that elevated serum titanium values are frequently found with the use of the Universal2 and Freedom being associated with often asymptomatic PPO in several patients, but the risk of loosening increased in implants older than 6 years, more than five PPOs, and serum titanium values between 26 to 31 µg/l [83]. PPO are commonly observed as well in 90% of cases one year after UHR around the collar of the uHead with it into the diaphysis pressfit inserted porous titanium coated stem (also found with all other UHR types), and PPO stabilized within three years postoperatively as well (Figures 2C/D, 5A3, 6A/C2 and 8C) [90][91][92]. Noted that the uHead including its option for total DRUJ replacement was withdrawn from the the marketplace by the company stryker (USA) in 2021 (prior offered by Small Bone Innovations / USA, financial interests?…”
Section: Failure Of Twr and Salvage Optionsmentioning
confidence: 77%
“…A newest study revealed that elevated serum titanium values are frequently found with the use of the Universal2 and Freedom being associated with often asymptomatic PPO in several patients, but the risk of loosening increased in implants older than 6 years, more than five PPOs, and serum titanium values between 26 to 31 µg/l [83]. PPO are commonly observed as well in 90% of cases one year after UHR around the collar of the uHead with it into the diaphysis pressfit inserted porous titanium coated stem (also found with all other UHR types), and PPO stabilized within three years postoperatively as well (Figures 2C/D, 5A3, 6A/C2 and 8C) [90][91][92]. Noted that the uHead including its option for total DRUJ replacement was withdrawn from the the marketplace by the company stryker (USA) in 2021 (prior offered by Small Bone Innovations / USA, financial interests?…”
Section: Failure Of Twr and Salvage Optionsmentioning
confidence: 77%